Control of microgrids : investigation on control of permanent magnet linear synchronous motor - Liu, Yanling (2016)
Nowadays, permanent magnetic linear synchronous motor (PMLSM) drive technology has been applied widely in various fields. The objective of this final year project is to study the mechanism of PMLSM and to develop a simulation model using direct force control. The mathematical model of PMLSM is presented by dq0-axes equations, which convert ordinary three-phase AC motor control to simulate DC motor control. Clarke and Park transformation algorithm could transform AC currents into current components on dq0-axes. Then, the space vector pulse width modulation (SVPWM) is used to control the stator current in order to improve performance of motor torque control. PID controller is introduced to adjust overshoot of the speed and shorten settling time. Meanwhile there are three closed loops: position loop, speed loop and current loop. The performance of the control system is tested by using MATLAB SIMULINK.